HUBUNGAN KUALITAS TIDUR DAN KEJADIAN ACNE VULGARIS PADA MAHASISWA - Pitoy, Frendy Fernando; Maramis, James Richard; Kawuwung, Christin Virginia (Universitas Sam Ratulangi, 2023)
Background: Acne vulgaris is a skin problem caused by excessive sebum or oil production which can cause inflammation and blockage of the pores. The emergence of acne vulgaris can be influenced by several factors, one of which is the quality of sleep. Objective: This study aims to determine the relationship between quality of sleep and the incidence of acne vulgaris in Nursing students at Universitas Klabat. Methods: This research is quantitative with a descriptive correlation method through a cross sectional approach. Total sampling technique was used with a sample of 90 people. Data was collected using a questionnaire, where the Pittsburgh Sleep Quality Index (PSQI) questionnaire was used to measure The quality of sleep, while the Global Acne Grading System (GAGS) questionnaire was used to measure the incidence of acne vulgaris.Results: The data analysis showed that most of the respondents' sleep quality was in the bad category with a total of 80 people (88.9%). While the level of acne vulgaris is mostly at a mild level with 70 respondents (77.8%). Bivariate analysis using Spearman's rho was used and it was found that there was no significant relationship between quality of sleep and the incidence of acne vulgaris in college students as proved by a p value > 0.05. conclusion: It is recommended for the students to balance the study and rest time to get the optimal sleep quality and it is also suggested to do facial care properly to prevent the acne vulgaris that is sustainable. For future researchers to be able to examine other factors that influence the incidence of acne vulgaris, such as a family history of acne, use of cosmetics, work, stress, lifestyle, and diet. Keywords: Acne Vulgaris, Quality of Sleep, Student.